Effect of two levels of AD3EC on the rumen environment of local lambs. - shteeb, huda (University of Thi-Qar Journal of agricultural research, 2025)
This study aimed to investigate the effect  of  two levels of AD3EC on the rumen environment  of  local  lambs  during the  period, from,2\1\2025 to 1\4\2025. The study was conducted at the Agricultural Station affiliated with the College of Agriculture and Marshes.  Twelve  local  sheep  lambs  at  weaning  age  were  purchased  and  divided  into  three  treatments,  with  four  lambs  per  treatment, having an  average  weight  of  13.00–13.55  kg.  The  first  treatment served as the  control  and  was  not administeredAD3EC,left for  comparison.  The  second  treatment received3 ml  of  AD3EC,  and  the  third  treatment received4 ml  of  AD3EC.  All  lambs  were  fed  the  same  diet.  The  results  showed  that  in  the  first,  second,  and  third  months  of  the  study,  there  was  a  significant  increase  in  pH  values  for  the  treatments receivingAD3EC compared  to  the  control  treatment. Additionally ,regarding total bacteria,  in  the  first,  second,  and  third  months,  there  was  a  significant  increase  in total bacterial  counts  for  the  treatments  that receivedAD3EC,compared to the control treatment